Driving innovation: When design collaboration becomes open source, how do reward mechanisms and in-process feedback act as catalysts - Boqun Xu; Kexin Xu; Yuning Zhu; Yiting Zhou; Xiaojian Liu (PLoS ONE, 2025)
Open innovation, prevalent in projects like design crowdsourcing, is widely acknowledged for its role in advancing technology through knowledge flow. However, the competitive nature of design teams often keeps core knowledge confidential, hindering collaboration in the field. Open-source ideation in software facilitates resource sharing, which has been demonstrated to overcome information barriers, fostering intellectual progress and driving remarkable outcomes. If applied to product design, could it make collaborative innovation more efficient or more difficult? External incentives are key in this dynamic. This study focuses on two representative motivational factors: reward mechanisms and transparent in-process feedback, and conducts a 2 × 2 experiment where designers completed multiple rounds of product colorization tasks with simultaneous resource exchange in an online environment. We evaluate design outcomes, collaborative referencing networks, and individual behaviors as key characteristics. Results indicate that the Quota Allocation Method (QAM) increases individual productivity (quantity) and competitive awareness, while the Contribution-Based Allocation Method (CAM) fosters creativity (quality) and long-term engagement, along with higher referencing density and satisfaction. Offering in-process feedback further optimizes collaboration outcomes but may introduce profit-driven behaviors in the CAM setting. By revealing the interaction between incentive mechanisms and individual motivations in open-source design collaboration, this study offers practical strategies to advance previous theories, promoting the effective implementation and sustainable collaboration of open-source models in product design.